2012
DOI: 10.1371/journal.pone.0041318
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Population in Northwestern Russia: An Update from Russian-EU/Latvian Border Region

Abstract: This study aimed to characterize the population structure of Mycobacterium tuberculosis in Pskov oblast in northwestern Russia, to view it in the geographical context, to compare drug resistance properties across major genetic families. Ninety M. tuberculosis strains from tuberculosis (TB) patients, permanent residents in Pskov oblast were subjected to LAM-specific IS 6110 -PCR and spoligotyping, followed by comparison with SITVITWEB and MIRU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 32 publications
5
24
0
6
Order By: Relevance
“…In the present study, the genotyping analysis revealed four lineages (Beijing, LAM, Haarlem and Ural) already reported in the FSU [17][18][19], although the Beijing family was more frequent (68%) in our study. Of interest, the combination of MIRU-VNTR and antibiotic resistance genotypes and phenotypes suggested that almost all strains defined as clustered by MIRU-VNTR were in fact distinct.…”
Section: Discussionsupporting
confidence: 48%
“…In the present study, the genotyping analysis revealed four lineages (Beijing, LAM, Haarlem and Ural) already reported in the FSU [17][18][19], although the Beijing family was more frequent (68%) in our study. Of interest, the combination of MIRU-VNTR and antibiotic resistance genotypes and phenotypes suggested that almost all strains defined as clustered by MIRU-VNTR were in fact distinct.…”
Section: Discussionsupporting
confidence: 48%
“…Нами впервые показано, что среди штаммов M. tuberculosis, выделенных от больных хрони-ческим туберкулезом легких в Ленинградской области, также превалируют представители генетического семейства Beijing, причем их доля возросла с 56, [3,6,9,11,15].…”
Section: Discussionunclassified
“…Распределе-ние штаммов LAM в Северо-Западном регионе России неоднородно. Так, если в Карелии и Ле-нинградской области их доля составляла 10,3% (что сопоставимо с Финляндией -7,3%), то в Псковской области превышала 20%, что близ-ко к показателю в Эстонии (17,8%) [1,3,18,24,25]. В Беларуси и Украине штаммы семейства LAM занимают второе место по распростра-ненности (около 23%) после Beijing и в структу-ре МЛУ штаммов (39,5 и 22,9% соответственно) [7,22,28].…”
Section: результаты и обсуждениеunclassified
“…Штаммы Ural (5,5%) были малочислен-ны, что сопоставимо с суммарными данными по СЗФО РФ и Финляндии [2,18,24]. В то же время в последние годы отмечен рост циркуля-ции ассоциированного с МЛУ субтипа семей-ства Ural в ряде стран Восточной Европы (Мол-дова, Литва) и на Северо-Западе России [2,15].…”
Section: результаты и обсуждениеunclassified